Language impoliteness among Indonesians on Twitter - Anwar, Miftahulkhairah; Amir, Fachrur Razi; Herlina,; Novi Anoegrajekti,; Liliana Muliastuti, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The presence of technology changes the way humans communicate in cyberspace compared to the real world. “Hootsuite We are social” research in January 2019 showed that there are approximately 150 million social media users in Indonesia or 56% of the total population. There has been an increase of 20 million social media users in Indonesia compared to last year. The extensive use of social media, including Twitter, is changing the news production platform. News is not only produced by mass media, but potentially by everyone who can produce reports, shape public opinion, and create a virtual society. This condition has a destructive power because it can quickly spread and provoke powerful emotions and heated discourse. This paper discusses the characteristics of Indonesian language impoliteness on Twitter using qualitative research methods. The data were collected from Twitter statuses of Indonesian users in 2018. The analysis showed that impoliteness in speech and language occurs because of the ideology and power of each speaker. The impolite speech in this research related to the impoliteness nuanced with contempt to ethnicity, religion, race, and to a social group. The impoliteness nuanced with insult to ethnicity was 20% of our observed samples, while impoliteness nuanced with religious contempt was 25.1%; impoliteness related to race was 18.3%; and impoliteness toward social groups was 36.6%. The impoliteness is also often caused by the stimulation of the occurring social and political causes at that time.